Silica-based bioactive solids obtained from modified diatomaceous earth to be used as antimicrobial filler material - Fernández, M. A. (2017)
It is well known that microbiological spoilage in indoor surfaces has a negative impact on human health. Antimicrobial functionalized materials are intensely studied. The present work seeks the synthesis of eco-friendly and cheap bioactive hybrid filler from diatomaceous earth (DE). The activation method used proved to be efficient to enhance the amount of quaternary ammonium groups supported by DE which was corroborated by spectroscopic methods and the thermogravimetry analysis. Zeta potential measurements reviled a bilayer arrangement of the ammonium groups on the functionalized solids and the bioassays showed their antimicrobial activity.